TGFβ and PTHrP Control Chondrocyte Proliferation by Activating Cyclin D1 Expression - Beier, Frank (The American Society for Cell Biology, 2001)
Exact coordination of growth plate chondrocyte proliferation is necessary for normal endochondral bone development and growth. Here we show that PTHrP and TGFβ control chondrocyte cell cycle progression and proliferation by stimulating signaling pathways that activate transcription from the cyclin D1 promoter. The TGFβ pathway activates the transcription factor ATF-2, whereas PTHrP uses the related transcription factor CREB, to stimulate cyclin D1 promoter activity via the CRE promoter element. Inhibition of cyclin D1 expression with antisense oligonucleotides causes a delay in progression of chondrocytes through the G1 phase of the cell cycle, reduced E2F activity, and decreased proliferation. Growth plates from cyclin D1–deficient mice display a smaller zone of proliferating chondrocytes, confirming the requirement for cyclin D1 in chondrocyte proliferation in vivo. These data identify the cyclin D1 gene as an essential component of chondrocyte proliferation as well as a fundamental target gene of TGFβ and PTHrP during skeletal growth.